1982
DOI: 10.1113/jphysiol.1982.sp014339
|View full text |Cite
|
Sign up to set email alerts
|

The electrogenic sodium pump in guinea‐pig ventricular muscle: inhibition of pump current by cardiac glycosides

Abstract: SUMMARY1. The inhibition of the electrogenic sodium pump in guinea-pig ventricular muscle by cardiac glycosides was studied with a voltage-clamp technique.2. Superfusion of the preparation with dihydro-ouabain (DHO) produced a reversible depolarization of up to 7 mV. When the membrane potential was clamped to a constant value near the resting potential application of DHO produced a corresponding current change in the inward direction which reached a steady state in less than 1 min.3. The drug-induced current c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 42 publications
6
28
0
Order By: Relevance
“…No significant difference was found between the slopes as in the previous experiment indicating that the glycoside had no effect on steady-state membrane conductance at a holding potential of -40 mV. This finding agrees with earlier reports for intact guinea pig myocardium 5 and sheep Purkinje fibers.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…No significant difference was found between the slopes as in the previous experiment indicating that the glycoside had no effect on steady-state membrane conductance at a holding potential of -40 mV. This finding agrees with earlier reports for intact guinea pig myocardium 5 and sheep Purkinje fibers.…”
Section: Resultssupporting
confidence: 92%
“…120 - 21 In contrast, however, a previous study on the effect of DHO on electrogenic Na-K pump current in guinea pig ventricular tissue 5 reported that the concentration-inhibition relation can be fitted by a linear Scatchard plot suggesting that functionally significant binding occurs at sites with a single affinity (A^D=' 46 /iM) only. Similarly, despite findings of apparent binding of cardiac glycosides at both highand low-affinity sites in canine cardiac tissue, 2 -8 inhibition by DHO of electrogenic pump current reported in isolated canine Purkinje myocytes suggests that only binding at a single affinity site (Ap-3.7 fiM) is associated with Na-K pump inhibition.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Since there is net outward movement of one positive charge with each cycle, an outward (hyperpolarizing) current is generated. The steady-state Na+-K+ pump current was studied by selective blockade of the transport process using the cardiotonic steroid dihydroouabain (DHO) (Isenberg & Trautwein, 1974;Daut & Rudel, 1982;Cohen, Falk & Mulrine, 1987), chosen because of its rapid onset and reversibility. The rate of Na+-K+ transport is regulated by the intracellular sodium concentration, [Na+]i, and the extracellular potassium concentration, [K+]0.…”
Section: Introductionmentioning
confidence: 99%
“…One functional enzyme form may exist according to the following different approaches : the electrophysiological properties of isolated myocytes [4], the Na+/K+-ATPase activity [5,6], the [3H]ouabain-binding sites on microsomal preparations with low Na+/K +-ATPase activity [7], gel electrophoresis mobility and immunoblotting with specific antibodies [8, 91, and the force of isometric contraction of ventricular strips induced by ouabain [5]. The highly controversial aspect of these data is reflected by the scattering of the IC50 values: the apparent sensitivity of the enzyme (or site) to ouabain has been estimated as 0.130 pM 171, 2.2 pM [6] and 46 pM [4]. …”
mentioning
confidence: 99%